2002
DOI: 10.1093/annonc/mdf178
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy for management of localised high-grade gastric B-cell lymphoma: how much is necessary?

Abstract: DLBCL of the stomach appears to be a highly chemosensitive disease. Our data question the need for full-term CHOP treatment in patients achieving CR upon first follow-up. However, recent data suggest that additional H. pylori eradication might have contributed to the excellent results achieved in our series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(22 citation statements)
references
References 17 publications
1
20
0
1
Order By: Relevance
“…32 Previous studies have shown that HPE combined with chemotherapy in gastric pure DLBCL patients can increase treatment efficacy compared with chemotherapy alone. 33 We also found that H pylori-positive gastric pure DLBCL patients displayed a lower rate of tumor progression, better tumor response to chemotherapy, and better overall survival than those without H pylori infection. 34 These findings indicate that H pylori-related gastric pure DLBCL may share common clinicopathological and biological features with H pylori-related gastric MALT lymphoma.…”
Section: H Pylori-positive Gastric Pure Dlbcl Is Dependent On H Pylorsupporting
confidence: 52%
“…32 Previous studies have shown that HPE combined with chemotherapy in gastric pure DLBCL patients can increase treatment efficacy compared with chemotherapy alone. 33 We also found that H pylori-positive gastric pure DLBCL patients displayed a lower rate of tumor progression, better tumor response to chemotherapy, and better overall survival than those without H pylori infection. 34 These findings indicate that H pylori-related gastric pure DLBCL may share common clinicopathological and biological features with H pylori-related gastric MALT lymphoma.…”
Section: H Pylori-positive Gastric Pure Dlbcl Is Dependent On H Pylorsupporting
confidence: 52%
“…As reported previously, H. pylori eradication resulted in durable histologically confirmed CR in 50-63% of patients with gastric DLBCL and concomitant MALT (35). The eradication of H. pylori may be necessary in PG-DLBCL, particularly in cases of concomitant MALT lymphoma (36).…”
Section: Discussionmentioning
confidence: 55%
“…The role of chemotherapy alone has been suggested because there are many active drugs. 6,36,37 Rituximab has clinical activity with a response rate of 73% and a median response duration of 10.5 months reported in 1 study. 38 However, a large retrospective study conducted by the International Extra Nodal Lymphoma Study Group (IELSG) analyzing the results of 180 patients did not find any difference in clinical outcome between initial localized treatment approaches with systemic chemotherapy.…”
Section: Discussionmentioning
confidence: 95%